Antioxidative Protective Effect of Ozone Therapy on Isolated Mitochondria from Human Sperm - Naserzadeh, Parvaneh; Shahi, Farshad; Izadi, Morteza (Journal of Antioxidant Activity, 2021)
Oxidative stress is implicated in male infertility and significantly higher reactive oxygen Species (ROS) are detected in 25% of infertile males. We showed that Ozone oxygen therapy (O2/O3) induces protective effects for oxidative stress factors and its consequences on isolated mitochondria obtained sperm which may provide insight into the role of Ozone oxygen in human infertility. The present study was carried out to further characterize and compare protective effect of Ozone oxygen on isolated mitochondria obtained from sperm. Semen was collected from human normal donors. We gained human sperm mitochondria by differential centrifugation and isolated mitochondria incubated with different concentrations (5µg/ml, 30 µg/ml, 80 µg/ml) of O2/O3. O2/O3 prevent significant decrease in reactive oxygen species formation and mitochondrial membrane potential collapse on isolated Human sperm mitochondria. Ozone oxygen therapy induced increase in ATP concentration on isolated mitochondria. Our findings showed that O2/O3 prevent toxicity in sperm, effect on mitochondrial respiratory chain and avoid to cytochrome c release and apoptosis signaling.
Keywords: Ozone/oxygen therapy; mitochondrial dysfunction; oxidative stress; Human spermatozoa; motility; anti-oxidative protection.